Research on power management and allowed propulsion control in pure electric vehicle - Junchao Jing (Elsevier, 2022)
For the optimization of vehicle mode management, the vehicle safety and the system efficiency, seven states which include initialization, the CPSR off, the CPSR on, HV contactor on, HV current enable, pre-crash and crash are presented based on the pure electric vehicle. The timing sequence of power up and power off in the normal working condition, the reset condition, the crash condition, OBC charge condition and emergency conditions are defined based on the states. Then the allowed propulsion is presented based on the ready driver, the ready HV system status, the immobilizer system and the feedback active drive cycle signal. Finally, the vehicle test result shows that the propulsion system manager can improve the driver’s comfort and reduce start time especially with a fast start which can be finished in 0.6 s of the whole power on process.